The first recorded fish-killing bloom in the Beibu Gulf, China: caused by dinoflagellate Karenia selliformis - Xu, Yixiao; Wang, Xi; Hörstmann, Cora; Dzhembekova, Nina; Zhu, Xueming; Neuhaus, Stefan; Tong, Mengmeng; Lan, Wenlu; John, Uwe (Frontiers in Marine Science, 2025)
The Beibu Gulf is located in the northwestern South China Sea. On August 2, 2023, a mass mortality event of cultured Trachinotus ovatus occurred in Lianzhou Bay and Tieshan Bay, suspected to be associated with a Karenia bloom. To identify the causative organism, investigate possible environmental drivers for bloom development, and determine the cause of fish mortality, in-situ bloom samples were collected for community characterization and toxicity analysis. Results showed that during the bloom, seawater quality remained within China’s highest classification, Class I, and RDA analyses indicated that protistan communities were primarily influenced by dissolved inorganic nitrogen (DIN) and pH. Based on a combination of microscopic observation, phylogenetic analyses of ITS and D1-D3 rDNA sequences obtained from clone libraries, and 18S rDNA V4 amplicon sequence variant (ASV) analysis, all approaches confirmed Karenia selliformis as the bloom-causing organism. Weak westward sea surface winds before and during the period facilitated the accumulation and probably the bloom formation of K. selliformis in Lianzhou and Tieshan coastal waters. A rabbit erythrocyte lysis assay detected hemolytic toxicity of 45.2–48.3% in tests with 5 × 107 rabbit erythrocyte cells exposed to 1.3–2.5 × 104 K. selliformis cells, suggesting it as a predominant factor in fish mortality. LC-MS/MS analysis did not detect neurotoxic shellfish toxins (BTX2, BTX3), diarrhetic shellfish toxins (DTX1-2, OA), or SPX1. However, gymnodimine-A (GYM-A), a “fast-acting” toxin known to be exclusively produced by K. selliformis, was detected at 2.2–2.5 pg GYM-A cell-1. To our knowledge, this study represents the first recorded fish-killing caused by a K. selliformis bloom in Chinese waters. The study provides the first biological and toxicity insights into K. selliformis bloom, crucial for the management and mitigation of fish-killing events associated to harmful algal blooms (HABs) in the Beibu Gulf and the South China Sea.